A novel photovoltaic system control strategies for improving hill climbing algorithm efficiencies in consideration of radian and load effect. (1st June 2018) - Liu, Hwa-Dong; Lin, Chang-Hua; Pai, Kai-Jun; Lin, Yu-Liang
Highlights: The proposed algorithm is still effectively in low irradiance level below 150 W/m 2 . We propose a fast accurate technique in consideration of the load and radian. A control strategy is employed to improve efficiency and reduce execution time. Abstract: This study proposes a novel algorithm for maximum power point tracking (MPPT) in solar-power-generating systems, and compares it with the conventional methods of hill climbing (HC). These conventional algorithms are prone to divergence under low irradiance levels (<150 W/m 2 ), resulting in maximum power point tracking difficulties and a limited effective maximum power point tracking range; the hill climbing algorithm in particular often entraps the actuating point near an inescapable local minimum and causes divergence. The proposed algorithm uses the angle between the sun and the horizon to develop a novel maximum power point tracking technique that extends the maximum power point tracking range to 100 W/m 2, effectively mitigating the divergence problems of the hill climbing algorithms when the irradiance level is low (<150 W/m 2 ). The performance of the proposed algorithm was compared with that of the hill climbing algorithm at varying irradiance levels, and the experimental results confirm the superiority of the proposed algorithm.